Problem Doktrin Relativisme (Studi Kritis Pemikiran Cendekiawan Muslim Indonesia) - Faisal Fauzi (Universitas Darussalam Gontor, 2018)
This research tries to explain the doctrine of relativism which is obviously related to Sophists. The author explains its definition, concepts, and logical consequences it has if if this doctrine infiltrates